ANALISIS NUMERIK KINERJA TURBIN ANGIN DARRIEUS TIPE H TERHADAP VARIASI JUMLAH BLADE DAN KECEPATAN ANGIN DENGAN PENDEKATAN SIMULASI CFD - Diki Afrianto; Andre Kurniawan; Yolli Fernanda; Fitrah Qalbina (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to analyze the aerodynamic performance of an H-type Darrieus wind turbine by varying the number of blades and wind speeds using the Computational Fluid Dynamics (CFD) method. The turbine geometry was modeled using SolidWorks 2022 and numerically simulated with ANSYS Fluent 2025. The models consist of three-blade and four-blade configurations employing the NACA 0012 airfoil profile, tested under three different freestream wind velocities: 7 m/s, 9 m/s, and 11 m/s. The simulations were conducted within static and rotating domains to examine the fluid flow characteristics around the rotor, including velocity distribution, pressure field, torque, and power efficiency. The results show that increasing wind speed leads to more complex and turbulent flow behavior, characterized by the emergence of vortex shedding behind the blades. The torque coefficient (Ct) and power coefficient (Cp) increased with higher wind speeds in the three-blade configuration, indicating greater energy conversion efficiency compared to the four-blade configuration. Conversely, the four-blade turbine exhibited reduced efficiency at higher wind speeds due to increased drag forces and inter-blade interactions, which caused energy losses. Overall, the findings demonstrate that the three-blade H-type Darrieus turbine provides superior aerodynamic efficiency and rotational stability at medium to high wind speeds, whereas the four-blade configuration performs better at lower wind speeds by generating higher starting torque. These results are expected to serve as a reference for the development of efficient vertical-axis wind turbine designs suitable for wind conditions in Indonesia.